2014
DOI: 10.3390/s140202619
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Aware Topology Control Strategy for Human-Centric Wireless Sensor Networks

Abstract: The adoption of mobile and ubiquitous solutions that involve participatory or opportunistic sensing increases every day. This situation has highlighted the relevance of optimizing the energy consumption of these solutions, because their operation depends on the devices' battery lifetimes. This article presents a study that intends to understand how the prediction of topology control messages in human-centric wireless sensor networks can be used to help reduce the energy consumption of the participating devices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Prediction techniques have been applied in several ways such as routing traffic reduction [24][25][26], energy efficient routing [27][28][29], or LQ estimation.…”
Section: Link and End-to-end Quality Prediction In Heterogeneous Netwmentioning
confidence: 99%
“…Prediction techniques have been applied in several ways such as routing traffic reduction [24][25][26], energy efficient routing [27][28][29], or LQ estimation.…”
Section: Link and End-to-end Quality Prediction In Heterogeneous Netwmentioning
confidence: 99%
“…These communication limitations have frequently been addressed using mobile ad hoc or opportunistic networks, as well as routing protocols on these networks [4][5][6]. These networks have low bandwidth and their topology is highly dynamic, and as such, they require the exchange of an goals, e.g., to support message delivery in mobile ad hoc networks (MANETs) [25][26][27][28], reduce the traffic [29][30][31] and keep the energy consumption in these infrastructures under control [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…These messages not only overload the communication links, but also increase the energy consumption of the nodes. The authors have also shown that the problem of delivering so much control information through the network can be addressed using predictions [29,31]. Particularly, the OLSRp protocol was proposed to eliminate redundant control information, and thus, reduce CPU and energy consumption in MANETs.…”
Section: Introductionmentioning
confidence: 99%
“…Prediction techniques have been applied in several ways such as routing traffic reduction [16], [17], [18], energy efficient routing [19], [20], [21] or LQ estimation.…”
Section: Link Quality Prediction In Community Networkmentioning
confidence: 99%